Designing cross‐linked pyrrole‐thieno [3, 4‐b] thiophene copolymer to push forward electrochemical performance and access flexible micro‐supercapacitor with ultra‐long cycling stability. (17th August 2021) - Wang, Min; Meng, Yupeng; Sun, Gengtian; Ma, Sijia; Qian, Ming; Duan, Mengna
Summary: While higher high specific surface area allows micro‐supercapacitor (MSC) electrode materials to have improved performance, it also tends to make them less stable thermodynamically and microstructurally, which can easily deteriorate and seriously affects their service life. So here, we have chosen a cross‐linked copolymer film structure as MSC electrodes. The pyrrole‐thieno [3, 4‐ b ] thiophene (TbT) copolymer film (namely PPy‐ co ‐TbT) exhibits high specific capacity, which can reach 47.8 mF cm −2 (a specific volumetric capacitance of 23.9 F cm −3 and a specific gravimetric capacitance of 28.1 F g −1 ) at a current density of 0.1 mA cm −2 using LiCl/PVA gel electrolyte with ultra‐long cycling stability (capacitance retention after 50 000 charge/discharge cycles is still higher than 93%, which is the leading level in MSCs). The electrochemical performance of this cross‐linked copolymer is superior to that of the single‐component polymer, achieving a 1 + 1 > 2 effect. Both features of cross‐linking and copolymerization have positive effects on microelectrodes requiring stable microstructures and high performance. The structurally stable cross‐linked copolymer obtained by copolymerization design may become a durable material for next generation ultra‐long‐life, high‐performance micro‐supercapacitor electrodes and will be widely developed. Highlights: The electrochemical performance of the cross‐linked copolymer electrode reaches 1 + 1 > 2. A pioneering cross‐linked copolymer was designed to prolong the stability of microsupercapacitor. Capacitance retention rate is still higher than 93% after 50 000 cycles, which is in the leading position. Provides an important thought for the manufacture of ultra‐long‐life microsupercapacitor. Abstract : A crosslinked copolymer structure (PPy‐ co ‐TbT) was designed as a flexible and long‐life electrode for micro‐supercapacitor.